Course And Management of Patients with Acute Promyelocytic Leukemia on The Background of Cytostatins (Eurasian Medical Research Periodical, 2023)
The number of patients who achieved complete remission, as well as the mortality rates during remission induction were wholly comparable to those previously obtained when using the 7+3+ATRA protocol: 90.3 and 9.7%, respectively. One patient in remission died (3.6% mortality rate). The likelihood of recurrence in this investigation was high (21%), which was due to gross noncompliance with maintenance therapy. On examining the clearance of the malignant clone by FISH and polymerase chain reaction, a naturally chimeric transcript identified by a molecular study was statistically significantly more frequently revealed during postinduction therapy, which was associated with different sensitivity of the techniques. Comparison of changes in the disappearance of a chimeric marker for APL with the AIDA and 7+3+ARTA programs showed that the clearance of the malignant clone was much slower.